Erratum. a novel approach to determining the alactic time span in connection with assessment of the maximal rate of lactate accumulation in elite track cyclists (International Journal of Sports Physiology and Performance, 2023)
TO OUR READERS: Several errors appeared in the following article: Dunst AK, Hesse C, Feldmann A, Holmberg HC. A novel approach to determining the alactic time span in connection with assessment of the maximal rate of lactate accumulation in elite track cyclists. Int J Sports Physiol Perform. 2023;18(2):157-163. https://doi.org/10.1123/ijspp.2021-0464